Ethnomathematics-Based Learning for Enhancing Mathematical Literacy in Junior High School Students - Muhammad Nurhusain; Karmila; Mulyati; Muhammad Tahir (Sains Global Institut, Indonesia, 2026)
Mathematical literacy remains a major challenge among Indonesian students, as reflected in national and international assessment results. This study aimed to examine the effect of an ethnomathematics-based learning model on the mathematical literacy skills of eighth-grade students at SMP Makassar Raya. A quantitative approach was employed using a pre-experimental One-Group Pretest–Posttest design. The participants consisted of 15 students selected through total sampling. Data were collected through a mathematical literacy test developed based on the PISA competencies of formulate, employ, and interpret. Descriptive and inferential statistics were used for data analysis, including the One-Sample t-test and Paired-Samples t-test. The findings revealed a substantial improvement in students’ mathematical literacy, with the mean score increasing from 18.13 on the pretest to 80.53 on the posttest. The One-Sample t-test indicated that the posttest mean score significantly exceeded the Minimum Mastery Criterion (Sig. = 0.003 < 0.05), while the Paired-Samples t-test confirmed a significant difference between pretest and posttest scores (Sig. = 0.000 < 0.05). These findings indicate that ethnomathematics-based learning contributes to the improvement of students’ mathematical literacy skills while promoting more meaningful mathematics learning that is relevant to cultural contexts.